(untitled) (Saptagandaki Journal, 2025)
Despite Nepal’s economic progress over recent decades, poverty remains a significant challenge. This study examines how different types of government spending affect poverty reduction in Nepal using data from 1990 to 2023. While previous research has looked at the general relationship between public spending and poverty, we lack clear evidence on whether social spending (health, education, social protection) or capital spending (infrastructure, roads, electricity) works better at reducing poverty in Nepal’s context. Using the Autoregressive Distributed Lag (ARDL) approach, we analyzed 34 years of data to understand both immediate and long-term relationships between government spending and poverty. Our findings show that social expenditure reduces poverty about twice as effectively as capital expenditure. Specifically, increasing social spending by 1% of GDP reduces poverty by 1.85 percentage points, while the same increase in capital spending reduces poverty by 0.93 percentage points. Economic growth remains the most powerful poverty-fighting tool, with each percentage point of growth reducing poverty by 2.16 percentage points. These results have important implications for Nepal’s budget planning, especially as the country implements its federal system and works toward eliminating poverty. The evidence suggests that while both types of spending help reduce poverty, social programs provide more direct and immediate benefits to poor people. This research offers practical guidance for policymakers trying to allocate limited budgets most effectively.